Cutaneous phaeohyphomycosis in a hematopoietic stem cell transplant patient caused by Alternaria rosae: First case report. Issue 3 (4th May 2017) - Liu, Amy W.; Bateman, Allen C.; Greenbaum, Adam; Garvin, Kanishka; Clarridge, Jill; Grim, Jonathan
Abstract: Alternaria species have been reported as a rare cause of fungal infection in organ and stem cell transplant recipients, but to date, no reports have been published of infection in humans caused by Alternaria rosae . Here, we report cutaneous A. rosae infection in a 66‐year‐old farmer with a history of primary myelofibrosis who had undergone allogeneic unrelated donor hematopoietic stem cell transplantation. Forty‐nine days post transplant, he presented with a nodule on the thumb with no findings suggestive of disseminated infection. Pathology, culture, and molecular speciation showed the nodule was caused by cutaneous A. rosae . He had been on voriconazole as antifungal prophylaxis, but was found to have a subtherapeutic voriconazole level. He was switched to posaconazole based on published in vitro data showing its superior efficacy in Alternaria treatment. Susceptibility testing showed that the A .  rosae isolate was indeed susceptible to posaconazole. His cutaneous lesion remained stable, but he died from respiratory failure secondary to lobar pneumonia. At lung autopsy, A. rosae was not identified in the lungs. We believe this to be the first published report, to our knowledge, of A. rosae infection in humans.